Manuel de Faria e Sousa en la encrucijada de las polémicas literarias: de las Anotaciones a las Rimas varias - Pérez- Abadín Barro, Soledad (El Colegio de México, 2025)
The purpose of this article is to elucidate the interpretative strategies employed by Faria e Sousa in his commentary on Camões’s Rimas varias. In his commentary he follows Herrera while censoring him, and also engages in the controversy surrounding Góngora, a poet whose major poems he condemns. His text, as will be seen, revives an exegetical tradition whose lesson and methods he intends to emulate. For him, Garcilaso prepared the advent of Camões, a figure who is seen as enthroned in timeless splendour. Such heights remain out of the reach of Góngora, who is barely present in censures tempered with praise. In his dialogue with previous controversies, Faria e Sousa reaffirms the value of his own critical and intellectual work.